2016
DOI: 10.5507/bp.2016.055
|View full text |Cite
|
Sign up to set email alerts
|

MMPs and TIMPs expression in facial tissue of children with cleft lip and palate

Abstract: Background and Aims. Morphogenesis of the upper lip and palate is a complex process involving highly regulated interactions between epithelial and mesenchymal cells. Genetic evidence in humans and mice indicates the involvement of matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs) in cleft lip palate (CLP) aetiology. This study investigated whether expression of MMP-2, MMP-8, MMP-9, TIMP-2, and TIMP-4, which are essential for the upper lip and palate fusion, is dysregulated in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Studies elsewhere have shown that small and large fibrils have distinct roles in stiff state, and only the small fibrils have a role in the disease states and hence lending to changing properties (Goh & Holmes, ), which could be the case in our medial tissues. Nonetheless, the possible role of factors apart from CF‐ED or a consequence of CF‐ED cannot be ruled out for compromised extracellular matrix of the medial tissue, based on previously described ability of metalloproteinases and their inhibitors to participate in matrix remodeling during lip fusion (Smane‐Filipova et al, ). We postulate that remodeling of the extracellular matrix components (collagen fibers and/or proteoglycans) that form the migration substrate for the cranial neural crest cells mesenchyme (Henderson & Copp, ; Jiang et al, ) could be different across the two sides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies elsewhere have shown that small and large fibrils have distinct roles in stiff state, and only the small fibrils have a role in the disease states and hence lending to changing properties (Goh & Holmes, ), which could be the case in our medial tissues. Nonetheless, the possible role of factors apart from CF‐ED or a consequence of CF‐ED cannot be ruled out for compromised extracellular matrix of the medial tissue, based on previously described ability of metalloproteinases and their inhibitors to participate in matrix remodeling during lip fusion (Smane‐Filipova et al, ). We postulate that remodeling of the extracellular matrix components (collagen fibers and/or proteoglycans) that form the migration substrate for the cranial neural crest cells mesenchyme (Henderson & Copp, ; Jiang et al, ) could be different across the two sides.…”
Section: Discussionmentioning
confidence: 99%
“…A fine modulation in the extracellular matrix in the orofacial region during development is essential for the cells to interact and respond to the remodeling or change in mechanical properties of the extracellular matrix (Gagliano et al, ; McDaniel et al, ), which is likely critical to cellular migration, differentiation (Badylak, ), and etiology of orofacial cleft (Mansell et al, ; Smane‐Filipova, Pilmane, & Akota., ). Studies in experimental models of fibroblast cells obtained from CL/P cases have suggested molecular mechanisms involved in phenotypic variation among fibroblasts (Bodo et al, ; Bosi et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“… IHC 100 , 102 , 106 NR NR MMP-9/Gelatinase B Extensively expressed in palatal mesenchyme, transiently upregulated while palatal shelves elevating and fusing. qRT-PCR, IHC, ISH Human and mouse: 24 , 102 , 104 Cleaves laminin NR MMP13 Before palate shelf elevation: in the palatal mesenchyme and basement membrane, intensified gradually in the nasal-medial part. During the palatal shelf elevation and the palatal shelf fusion: intensified gradually in the tip and nasal-medial part and MES After the palatal shelf fusion: still strong in the nasal-medial mesenchyme and MES but decreased in other area.…”
Section: Ecm Remodeling By Extracellular Metalloproteinasesmentioning
confidence: 99%
“… IHC 100 NR NR TIMP-3 Palatal epithelium, transiently expressed in mid-oral and ventral-medial mesenchyme. IHC 100 NR NR TIMP-4 Oral mucosa IHC 104 NR NR ADAMTS ADAMTS9 Palatal capillary endothelium ISH 12 Versican Haploinsufficiendy of Adamts9 in Adamts20 mutant mice ( Adamts9 ± ;Adamts20 bt/bt ) Complete cleft palate 12 ADAMTS20 Palatal mesenchyme ISH 12 NR, not reported. IHC, immunohistochemical staining.…”
Section: Ecm Remodeling By Extracellular Metalloproteinasesmentioning
confidence: 99%